Preferensi Mahasiswa Dalam Memilih Rumah Kos (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Nisak, Khoirun; Pardiman, Pardiman; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The development of universities in Indonesia has implications for increasing the number of students. The tendency of the majority of students who are transmigrants in related university areas has a further impact on increasing the need for temporary housing. Differences in perception and background give rise to different characteristics of boarding house needs. There are several types of boarding houses with characteristics and according to their individual needs. This study tries to examine several housing preferences that are in accordance with the demands and desires of students. This is useful in providing boarding house occupancy for students and comparing the level of importance of respondents to each key attribute in each type of boarding house. This is also useful as the provision of more appropriate student housing according to the main characteristics of student demand. Data collection was carried out using questionnaires which distributed to 135 students of the Islamic University of Malang. This exploratory research data was then carried out quantitatively using conjoint analysis. The results showed that the attributes of the first order of price, second room facilities, third environmental conditions, fourth security, fifth completeness of public facilities, sixth location and the last order is social environment. Keywords: Preferences,Boarding House, Student